2021
DOI: 10.3390/app11199296
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Performance Measurement of Public Educational Institutions Using Machine Learning Models

Abstract: Lack of education is a major concern in underdeveloped countries because it leads to poor human and economic development. The level of education in public institutions varies across all regions around the globe. Current disparities in access to education worldwide are mostly due to systemic regional differences and the distribution of resources. Previous research focused on evaluating students’ academic performance, but less has been done to measure the performance of educational institutions. Key performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…ML techniques have also been shown to be beneficial in improving outcomes at several educational institutions and student management centers by making necessary educational information readily available to students and other individuals [34,35]. In the past 10 years, investigations on ML and education data mining [EDM] have played a significant role in exploring educational problems [31,36], such as understanding student performance [37,38] and educational institution performance [39]. These techniques have also been used to predict student engagement and difficulty in online education [40,41] and in recommending suitable colleges and courses [9,[42][43][44][45].…”
Section: Machine Learningtechniques Used In An Education Predictive M...mentioning
confidence: 99%
“…ML techniques have also been shown to be beneficial in improving outcomes at several educational institutions and student management centers by making necessary educational information readily available to students and other individuals [34,35]. In the past 10 years, investigations on ML and education data mining [EDM] have played a significant role in exploring educational problems [31,36], such as understanding student performance [37,38] and educational institution performance [39]. These techniques have also been used to predict student engagement and difficulty in online education [40,41] and in recommending suitable colleges and courses [9,[42][43][44][45].…”
Section: Machine Learningtechniques Used In An Education Predictive M...mentioning
confidence: 99%
“…A model has been suggested to estimate the institutional performance based on key performance indicators using data mining techniques. The results showed that the artificial neural networks performed better in achieving accuracy (i.e., 82.9%) in comparison to other machine learning models employed in the study [59]. The student performance in a learning management system based on behavioral features was predicted by applying ensemble methods including bagging, boosting, and random forest to augment the performance of classifiers.…”
Section: Comparison Of Applied Approach With Existing Approachesmentioning
confidence: 99%
“…Deep learning methods have arrived at competitive performances, compared with the traditional techniques, in a short time. They have been shown to be a potential tool for growth, even for mature fields with a higher bar of entry for new approaches, such as communication [3,4]. Deep learning has exhibited its problem-solving potential and growth in mobile traffic classification, as well.…”
Section: Introductionmentioning
confidence: 99%